2019
DOI: 10.1002/ieam.4117
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of potential bias in the sensitivity of toxicity data used to construct sensitivity distributions for copper

Abstract: Since the mid‐1970s, thousands of studies have evaluated the toxicity of various chemicals to aquatic organisms. Results from many of these studies have been used to develop species sensitivity distributions (SSDs) or genus sensitivity distributions (GSDs) for deriving water quality guidelines. Recently, there has been more emphasis on evaluating the toxicity of chemicals to sensitive organisms rather than the entire range of sensitivities. The SSD approach is intended to inform the derivation of guidelines fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Responses from these tests nearly span the entire distribution of existing data for all 4 metals, with the mayfly responses extending the sensitive tail of the distributions for Cd, Cu, and Zn. The new community responses incorporated directly into the SSDs could address the imbalance that could develop when testing of “new” species tends to target potentially sensitive taxa, which over time could skew the (debatable) concept that compiled laboratory SSDs are representative of the distribution of sensitivities in natural environments (Croteau et al 2019). Further, these results refute analyses of toxicological databases which reported that aquatic insects were the most metal‐tolerant group of the aquatic macroinvertebrates (Malaj et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses from these tests nearly span the entire distribution of existing data for all 4 metals, with the mayfly responses extending the sensitive tail of the distributions for Cd, Cu, and Zn. The new community responses incorporated directly into the SSDs could address the imbalance that could develop when testing of “new” species tends to target potentially sensitive taxa, which over time could skew the (debatable) concept that compiled laboratory SSDs are representative of the distribution of sensitivities in natural environments (Croteau et al 2019). Further, these results refute analyses of toxicological databases which reported that aquatic insects were the most metal‐tolerant group of the aquatic macroinvertebrates (Malaj et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Water quality criteria and risk assessments commonly rely on species sensitivity distributions (SSDs) compiled from laboratory toxicity data sets. Reliable values for aquatic insects in SSDs are scarce, comprising approximately 1 to 2 of the taxa out of the 20 to 30 chronic taxa values which commonly populate metal SSD data sets (Brix et al 2005; Mebane 2006; DeForest and Van Genderen 2012; Croteau et al 2019). For instance, Brix et al (2011) found only 9 laboratory toxicity studies testing aquatic insects from 2000 to 2010 compared to hundreds of papers published with other aquatic taxa over the same time frame.…”
Section: Introductionmentioning
confidence: 99%